The genus Butia (Arecaceae) with emphasis on the species Butia exilata and Butia lallemantii: a review (Research, Society and Development, 2020)
The Arecaceae family is considered the third largest botanical family, with a predominantly pantropical distribution. Among its genera, the Butia genus stands out, which differs from the others in that it presents an upward disposition of conduplicated leaflets and the presence of pores in the endocarp. The Butia genus has potential in the production of hearts of palm, oils, starch, waxes, fibers and in food. However, there is little scientific information that can contribute to the species of this genus being used as a genetic resource in the expansion of family farming, in the diversification of agribusiness, in the development of cultural handicrafts and in regional cuisine. In addition, many species of this genus are threatened with extinction and studies on their current state and conservation measures are of great importance. The work demonstrates that the evolutionary relationship within the genus Butia is not well resolved and there are divergences between authors regarding genetic variability within and between populations. The restricted geographical distribution and the divergences in scientific information on the genus Butia represent preponderant conditions for the search for understanding in future works on the ecological characterization, genomics and conservation measures of the species Butia exilata and Butia lallemanti, the only palm trees with the cespitoso habit belonging to the genus Butia.